Growth patterns and ecological classification of Tor tambra (Valenciennes 1842) in the Mamis River, Leuser Ecosystem Area, Aceh Province, Indonesia - Akmal, Yusrizal; Yunus , Muchammad; Plumeriastuti , Hani; Dhamayanti, Yeni; Irfannur; Muliari; Zulfahmi, Ilham; Batubara, Agung Setia (Faculty of Fisheries and Marine Universitas Airlangga, 2024)
Graphical Abstract Highlight Research 1. Tor tambra is the most dominant species other Tor species in Aceh Province, Indonesia. 2. The population of T. tambra has decreased significantly due to overfishing and environmental destruction. 3. This research aims to examine the habitat characteristics, growth patterns and condition factors of T. tambra. 4. Analysis of the length weight relationship of T. tambra revealed that the condition of the fish was stable . Abstract This research was aimed to examine the habitat characteristics, growth patterns and condition factors of T. tambra in the Mamis River, Leuser Ecosystem Area, Aceh, Indonesia. This research was conducted on the Mamis River in three different river conditions from July to August 2023. The ecological parameters of T. tambra were conducted by observing the main, broodstock, spawning, and nursery ground habitats based on diversity of catch size at a location, water quality, aquatic substrate, aquatic vegetation, and water shade. The growth pattern parameter was also analyzed to reveal the condition of T. tambra. The T. tambra habitat in the Mamis River includes broodstock and spawning habitat with the criteria from small to large rocks overgrown with Bryophytes, gravel and sand substrates, clear water color, slow to swift water currents, and river environment most of it is primary forest. In the main habitat, there is dominant riparian vegetation in the form of forest timber trees such as Pometia pinnata, Ficus fistulosa, Hydnocarpus castanea, and Aglaia tomentosa. The habitat for the juvenile is in the form of rocks, gravel substrate, clear water color, and fast water currents. In the nursery habitat, the dominant riparian vegetation is Balakata baccata. Based on the results of water quality analysis at the three stations, it shows that temperature, pH, DO, currents, BOD, COD are significantly different, but brightness levels are not significantly different. Based on the analysis of the length-weight relationship, it shows that the condition of the fish is stable with sufficient food availability.